(untitled) (Journal of Basic and Applied Sciences, 2023)
In recent years, sustainability in construction has become a major priority due to its numerous benefits. The world is increasingly moving toward sustainable development, making sustainable construction of paramount importance in the building industry. In response to environmental challenges, there is a growing global trend toward constructing buildings with sustainable materials, which helps reduce pollution and improve the current environmental situation. This article aims to propose an effective strategy for assessing the feasibility of implementing sustainability standards in construction while identifying the challenges and opportunities associated with achieving sustainable buildings. Its primary objective is to explore how reconstruction can be integrated into development plans in a way that improves current conditions, preserves history, heritage, and identity, and incorporates sustainability principles into reconstruction projects. Any reconstruction strategy should be comprehensive, preventive, and integrated within broader development plans. It should aim to achieve sustainable reconstruction while maintaining the flexibility needed to adapt to emergency circumstances. Among its key objectives are ensuring comprehensive reconstruction that addresses all aspects of the urban environment, achieving sustainable reconstruction that preserves national identity, history, and cultural heritage, and actively involving all sectors of society throughout every stage of implementation.